Modulating taste perception through color and shape: a mixed reality study on solid foods - Guberman, Mariela; Sakdavong, Jean-Christophe; Galmarini, Mara V. (Frontiers in Computer Science, 2025)
The study explores the cross-modal correspondence between color and taste in a mixed reality (MR) context. Using dehydrated apple snacks, we examined how product and context color influence the perception of sweetness and sourness. Three experiments were tested: the effect of product color, the effect of shape and color of context, the effect of congruent product and context color and shape. A 2-alternative forced choice (2-AFC) test was conducted with 102 participants to assess taste perception. Results showed no significant differences for product or context color alone. However, in the third experiment, participants selected consistently the green snack in the green angular context as the sourest, demonstrating the importance of sensory congruence. Conceptually, participants associated red and pink with sweetness (70%), green and yellow with sourness (68%). Additionally, over 90% linked rounded shapes to sweetness and angular shapes to sourness. The study highlights how visual stimuli and shape can influence solid food taste perception, with MR providing a valuable tool for controlling sensory inputs.